Purchase intention related to legitimacy, uncertainty and innovation - Delso Vicente, Alberto Tomás; Aguado-Tevar, Oscar; Diaz-Marcos, Luis; Almonacid-Durán, Margarita (Revista de Ciencias Sociales, 2024)
There is currently a growing interest in understanding the purchase intention and acceptance of electric vehicles. In this regard, this study aims to analyze the factors that influence the context of sustainable mobility, focusing on purchase intention, perception of innovation, perception of legitimacy and uncertainty. A systematic literature review methodology was employed, covering articles published since 2005 in English and Spanish. The main results revealed a positive correlation between the availability of government incentives and purchase intention of electric vehicles, as well as the importance of effective communication of innovation to increase adoption. Furthermore, the relevance of uncertainty management and legitimacy as key factors was highlighted. In conclusion, these results have significant implications for the formulation of communication strategies, government incentive policies and the improvement of charging infrastructure to promote the adoption of electric vehicles and sustainable mobility.